Sources of Indonesia Manufacturing Productivity Growth - Wulandari, Rini; Prasetyo, Alvin Sugeng; Susandika, M Devis (Universitas Pasundan, 2024)
Manufacturing industry productivity is a basic element in Indonesia's economic progress, so it is needed to accelerate Indonesia's economic growth. The advantage of the Manufacturing industry sector is that it has forward and backward linkages between sectors so that through manufacturing industry development, Indonesia higher economic growth. This research examines and analyzes the sources of manufacturing industry productivity growth in Indonesia for the 2010-2022 period. The research method used is panel data regression. The estimation results show that based on the panel data regression results the selected model is the FEM model so that all independent variables (raw materials, labor, energy, and capital) have a significant positive effect on the output of the Indonesian manufacturing industry. The estimation results in this study also found that labor and capital are inelastic.